Photodegradation of 2,4-Dichlorophenol in Aqueous Systems under Simulated and Natural Sunlight - Dorota Gryglik; Marta Gmurek; Magdalena Foszpańczyk; Stanisław Ledakowicz (International Journal of Photoenergy)
The work presents results of studies on 2,4-dichlorophenol (2,4-DCP) degradation in aqueous solutions using photochemically initiated processes by simulated and natural sunlight. A number of possible substrate photodegradation routes were investigated, by both direct photolysis and photosensitized oxidation process. The major role of singlet oxygen in 2,4-DCP photodegradation was proved. Rose Bengal and derivatives of porphine and phthalocyanine were used as sensitizers. The influences of various process parameters on the reaction rate were investigated. On the basis of experimental data reaction rate constants of 2,4-DCP photosensitized oxidation were determined. The possibility of using natural sunlight to degrade 2,4-DCP in water in the middle latitudes was stated. The acute toxicity bioassay was conducted with the marine bacterium Vibrio fischeri as a bioluminescent indicator. The obtained results encourage further research on this process.